Lung adenocarcinoma and pulmonary actinomycosis: a cautionary tale. Issue 6 (December 2021) - Drozdowicz, Kelly; Marquez, Hector A.; Burks, Eric J.; Suzuki, Kei
Background: Pulmonary actinomycosis is a rare and slowly progressive bacterial infection that is often mistaken for lung cancer. Multiple case reports caution against premature diagnosis of malignancy without proper consideration of potential Actinomyces infection. However, no cases in the English literature have been reported that demonstrate the possible coexistence of Actinomyces and lung cancer. Case Description: We present two cases of patients with culture-positive Actinomyces who were later found to have concomitant biopsy-proven lung adenocarcinoma. Conclusions: In the workup of a newly identified lung mass, positive culture for Actinomyces does not rule out an underlying malignancy.